Effect of ausforming on mechanical properties of 12%Cr ferritic/martensitic steel - Kislyak, I.F.; Rostova, H.Yu.; Andrievskaya, N.F.; Kalchenko, A.S.; Okovit, V.S.; Tikhonovsky, M.A.; Vasilenko, R.L.; Tantsiura, I.G.; Panov, V.A. (Вопросы атомной науки и техники, 2022)
Effects of ausforming through upsetting at 890 °C and following tempering on microstructure and mechanical properties under uniaxial tension of 12CrWMoNbVB ferritic/martensitic steel are studied. Electron microscopic investigations along with elemental analysis of the steel samples in various states provided detailed information about subgrain structure and typical precipitates, the latter mainly М₂₃С₆ and NbC carbides. Strength and plasticity parameters (σ₀, σb, δ) are examined and shown to enhance under applied thermomechanical treatment as compared to standard characteristics of the steel. Preferred treatment of the steel is preliminarily evaluated. Досліджено вплив аусформінгу шляхом осаджування при 890 °C та подальшого відпускання на мікроструктуру і механічні властивості за одновісного розтягу феритомартенситної сталі 12CrWMoNbVB (18Х12ВМБФР – за ГОСТ 5632-72). Електронно-мікроскопічні дослідження, а також елементний аналіз зразків сталі в різних станах дозволили отримати детальну інформацію про субзеренну структуру та типові виділення. Останні переважно представлені карбідами М₂₃С₆ та NbC. Досліджено параметри міцності та пластичності (σ₀, σb, δ), котрі покращуються після застосованої обробки у порівнянні зі стандартними характеристиками сталі. Попередньо оцінено переважну обробку сталі. Исследовано влияние аусформинга путем осадки при 890 °C и последующего отпуска на микроструктуру и механические свойства при одноосном растяжении ферритомартенситной стали 12CrWMoNbVB (18Х12ВМБФР – по ГОСТ 5632-72). Электронно-микроскопические исследования, а также элементный анализ образцов стали в различных состояниях позволили получить подробную информацию о субзеренной структуре и типичных выделениях. Последние в основном представлены карбидами М₂₃С₆ и NbC. Исследованы параметры прочности и пластичности (σ₀, σb, δ), которые улучшаются при применяемой термомеханической обработке по сравнению со стандартными характеристиками стали. Предварительно оценивается предпочтительная обработка стали.